Willing Collaborators: The Long Game - Keane, Michael (Media, Culture and Communication in Asia-Pacific Societies, 2018)
As China looks to reinvigorate its soft power by drawing on the creative inputs of foreign media producers and technical expertise, this book explores how and why creative workers are moving to the Mainland from East Asia, and how they are ...